The Datafication Challenge. Introduction to Themed Issue - Joke Hermes; Julia Conemans; Rachel Somers Miles; Kuba Piwowar (VIEW Journal of European Television History and Culture)
Inspired by the MediaNumeric project, this issue of VIEW will take a closer look at the challenges journalists and multimedia makers face in a datafied world and how they might be trained to deal with them. The central question being how datafication for professionals is a multi-faceted challenge given diminishing trust in institutions and professionals, including misgivings and hope for data among journalists and the general public alike. This issue therefore explores how professionals might find help in not only coming to terms with datafication and algorithmic logic but also build it into a strength for public-minded news and documentary storytelling.